Artful Diffractions: (En)tangling with Reflexivity and New Materialist Philosophy - Flint, Maureen; Wang, Yixuan (Art/Research International)

(untitled) (University of Alberta, 2024)
In this article, we explore the potential of artmaking as a reflexive practice, grounded in the work of feminist new materialist philosophers Karen Barad and Donna Haraway. Barad and Haraway’s philosophies emphasize our entanglement with more-than-human materialities and forces and consider our ethical responsibility to the world. We explore our own artful practices such as collaging, drawing, mapping, and creative writing as reflexive practices that help us consider who we are in relation to our research. These examples provide a grounded description for novice and veteran researchers alike who might be interested in using artful reflexive practices in their own work.